Environmental management and valorization of cultivated tobacco stalks by combined pretreatment for potential bioethanol production - Karn Sophanodorn (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Expanding concern over exhausting fossil fuel and nursery gas limits must lead the more intrigued in renewable fuel-making from biomass sources counting sugars, starches, and lignocellulosic materials. Cultivated tobacco stalk is one of the massive amounts of available biorefinery wastes. Therefore, tobacco stalk was used for bioethanol production in this study. It contains abundant chemical compounds including cellulose, hemicellulose, and lignin 35.45 ± 0.13(%), 43.90 ± 0.26 (%), and 18.16 ± 0.28 (%), respectively. The total and reducing sugar utilizing phenol-sulfuric and DNS methods were carried out before and after the bioethanol fermentation process. Also, the combined pretreatment process was used for the degradation of the biomass and better accessibility to available sugars to increase the bioethanol production. Hydrolysate with the highest sugar concentration was selected and proceeded to bioethanol fermentation for 72 h. From the experimental results obtained, the total and reducing sugar concentration of tobacco stalk was 27.97 g/L and 5.43 g/L, individually. The results revealed the highest ethanol yields 75.74 (g/L) was reached at 48 h fermentation. Consequently, this form of combined pretreatment technique is a promising method of increasing the overall yield in the dried tobacco stalks to the bioethanol production process.